The role of co-parenting alliance as a mediator between trait anxiety, family system maladjustment, and parenting stress in a sample of non-clinical Italian parents - Delvecchio, Elisa; Sciandra, Andrea; Finos, Livio; Mazzeschi, Claudia; Riso, Daniela Di (Frontiers in Psychology, 2015)
This study investigated the role of co-parenting alliance in mediating the influence of parents’ trait anxiety on family system maladjustment and parenting stress. A sample of 1606 Italian parents (803 mothers and 803 fathers) of children aged one to thirteen years completed measures of trait anxiety (State Trait Anxiety Inventory - Y), co-parenting alliance (Parenting Alliance Measure), family system maladjustment (Family Assessment Measure - III), and parenting stress (Parenting Stress Inventory - Short Form). These variables were investigated together comparing two structural equations model-fitting including both partners. A model for both mothers and fathers was empirically devised as a series of associations between parent trait anxiety (independent variable), family system maladjustment and parenting stress (dependent variables), mediated by co-parenting alliance, with the insertion of cross predictions between mothers and fathers and correlations between dependent variables for both parents. Results indicated that the relation between mothers and fathers’ trait anxiety, family system maladjustment and parenting stress was mediated by the level of co-parenting alliance. Understanding the role of couples’ co-parenting alliance could be useful during the family assessment and/or treatment, since it is an efficient and effective tool to improve the family system maladjustment and stress.